STRATEGI PENINGKATAN KWALITAS PEMBERANGKATAN PEKERJA MIGRAN INDONESIA (PMI) - Wahid Erawan (IKIP Siliwangi, 2021)
This paper is the result of a literature study which is expected to be of benefit to academics, both students and lecturers, and it is also hoped that the relevant agencies can improve the quality of the departure of Indonesian migrant workers. Sometimes we neglect our duties and responsibilities, one of which is not paying attention to PMI's skills / expertise and only pursuing quota fulfillment targets. So that we need a good planning model between PMI, and a training place to improve the quality of PMI shipments in order to reduce PMI problems abroad. From the various existing literature, mapping strategies to improve the quality of migrant workers must follow the existing rules. From here it is not uncommon for the government, the private sector, or related agencies to encounter obstacles. In this study, the approach used is a qualitative approach, especially by using a systematic procedure for reviewing or assessing documents. The skills / expertise of prospective PMI need to be improved and supervision from the relevant government. In the future, we need a good planning model for training places to improve the quality of PMI shipments in order to reduce PMI problems abroad.